GERAKAN PENGEMBANGAN MINAT BELAJAR BAHASA ARAB DI MADRASAH AL-AMANAH DESA SUTAWINANGUN - EKO PRIYANTO Eko; Agus Hidayat Taupik agus; Esa Thahara esa; Dhurotul Mufidah upi; Sofandi (Al Naqdu, 2023)
ABSTRACKArabic is one of the subjects that is generally always studied by students in a madrasa. This study aimsto develop students' interest in learning Arabic and madrasah al-Amanah students. In student work activitiesheld in Sutawinangun Village, we IAI Cirebon students found problems or problems in one of the madrasas inSutawinangun village, namely at the al-Amanah madrasa, where at the madrasa there were still no Arabicsubjects which usually always exist in every madrasa. Without Arabic subjects, this will affect students'understanding of the meaning of the prayers or letters in the Qur'an which they always deposit every week. Themethod used in writing this journal is community service. The first thing we did was ask permission from theteachers at the al-Amanah madrasa to teach Arabic to their students. After getting permission, we immediatelystarted the lesson and it was held every Saturday afternoon at the al-Amanah madrasa. From these activities,we were able to build and develop interest in learning Arabic among the students of the al-Amanah madrasawhich later after the KKM period ended, the Arabic language learning would be continued by the teachers atthe al-Amanah madrasa.Keywords: Arabic; Interest; Devotion; Al-Amanah Madrasa.